Learned Helplessness and Associated Factors Among Patients with Lung Cancer - Huang F; Shi Y; Ding L; Huang J; Zhang Z (Patient Preference and Adherence, 2024)
Fengmei Huang,1,* Yumei Shi,1,* Li Ding,2 Jingui Huang,1 Zhaoli Zhang2 1Department of Medical Oncology, Chongqing University Cancer Hospital, Chongqing, 400030, People’s Republic of China; 2Nursing Department, Chongqing University Cancer Hospital, Chongqing, 400030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhaoli Zhang, Nursing Department, Chongqing University Cancer Hospital, No. 181 Hanyu Road, Shapingba District, Chongqing, People’s Republic of China, Tel +86-23-65079129, Email 2671004746@qq.comPurpose: Learned helplessness (LH) is the psychological state in which an individual experiences multiple failures and setbacks and experiences a sense of loss when facing the current situation. It is a significant burden for lung cancer patients that can impair quality of life and lead to physical, social, and psychological difficulties. Thus, this study aimed to determine the level of LH among patients with lung cancer and identify factors associated with LH.Patients and Methods: From August 2022 to March 2023, 237 patients with lung cancer from Chongqing University Cancer Hospital were selected for this study. A general information questionnaire, the LH scale, the Brief Illness Perception questionnaire, the Strategies Used by People to Promote Health questionnaire, the Medical Coping Modes questionnaire, and the Self-esteem scale were used for the investigation. Multiple linear regression was employed to identify influencing factors for LH in patients with lung cancer.Results: The total LH score of patients with lung cancer was 52.19± 11.20. Multiple linear regression analysis showed that illness perception (β=0.249, P=0.001), self-efficacy (β=− 0.194, P=0.017), and resignation coping mode (β=0.267, P< 0.001) were the main influencing factors of LH (P< 0.05), which explained 42.0% of the total variance.Conclusion: The score of LH in patients with lung cancer was at a moderate level in this study. Illness perception, self-efficacy, and resignation coping mode have been found to impact LH among patients with lung cancer. Healthcare professionals should implement effective interventions, such as promoting self-efficacy, encouraging positive coping, and reducing illness perception, to alleviate LH.Keywords: lung cancer, learned helplessness, risk factors, psychology